Achieving Universal Primary Education in Uganda : The ‘Big Bang’ Approach - Bertoncino, Carla; Murphy, Paud; Wang, Lianqin (World Bank, Washington, DC, 2012)
Uganda's primary enrollment rates have risen remarkably since 1996, when the Government eliminated fees in a bold attempt to achieve universal primary education. But the massive expansion in numbers has affected the quality of education; and it will be a major challenge to cope with the rising demand for post-primary education. Key lessons learned include: Successful education reform in developing countries like Uganda require high levels of political and education management commitment that is sustained over a long period. The big bang approach can be a very powerful policy instrument for getting all the children into school and Uganda had managed to do this very well. Timely, flexible donor support is a critical factor.